2001
DOI: 10.1103/physrevlett.86.4504
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Photofragmentation of CO: A Selective Probe of Core-Level Resonances

Abstract: Anion-yield spectroscopy using x rays is shown to be a selective probe of molecular core-level processes, providing unique experimental verification of shape resonances. For CO, partial anion and cation yields are presented for photon energies near the C K edge. The O- yield exhibits features above threshold related only to doubly excited states, in contrast to cation yields which also exhibit pronounced structure due to the well-known sigma* shape resonance. Because the shape resonance is completely suppresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 38 publications
3
65
1
Order By: Relevance
“…The monochromator resolution achieved at 204 eV photon energy was estimated as 30 meV, using previous measurements of the 4s͑ 3 D͒ 2 D 5/2 atomic chlorine transition at 204.31 eV with a theoretical lifetime broadening of 5.3 meV. 9 The resolution at h = 300 eV was estimated as 70 meV based on previous measurements of CO. 2 Ion mass and charge characterization was done with a 180°hemi-spherical analyzer with a resolution of 1 mass in 50. 10 Briefly, the fragments are created by interaction with the light beam at the exit of an effusive gas jet.…”
Section: Methodsmentioning
confidence: 99%
“…The monochromator resolution achieved at 204 eV photon energy was estimated as 30 meV, using previous measurements of the 4s͑ 3 D͒ 2 D 5/2 atomic chlorine transition at 204.31 eV with a theoretical lifetime broadening of 5.3 meV. 9 The resolution at h = 300 eV was estimated as 70 meV based on previous measurements of CO. 2 Ion mass and charge characterization was done with a 180°hemi-spherical analyzer with a resolution of 1 mass in 50. 10 Briefly, the fragments are created by interaction with the light beam at the exit of an effusive gas jet.…”
Section: Methodsmentioning
confidence: 99%
“…In the twoand three-atomic cases mentioned above [12,13,14,15,16,17,18,19], anion yield has been found to be suppressed at shape resonances. However, in the case of SF6, anion yield of similar relative intensity as in cations has been observed at the position of the shape resonance, both by Scully et al [22], and by some of us [23].…”
Section: Introductionmentioning
confidence: 88%
“…We have conducted a systematic study of partial positive and negative ion yields on as many as twenty molecules, which has allowed us to establish several criteria for spectral assignment based upon some peculiar features of partial ion yield experiments. Among these are CO [12,13], CO 2 [14], H 2 O [15], OCS [16], N 2 O [17], NO [18], H 2 S [19], and CHOOH [20]. In particular, we have demonstrated that in relatively small systems the anion yield in correspondence of shape resonance-related spectral features is negligible, due to the difficulty of producing a negatively charged species starting from a species with a double positive charge, resulting from mechanisms like normal Auger decay [12].…”
Section: Introductionmentioning
confidence: 99%
“…The results are compared to an early time-of-flight photoionization mass spectrometry study, in which a very short extraction pulse was used to improve quantitative collection (6), and to (e,e + ion) coincidence measurements (7) simulating photoionization, which are generally accepted to produce branching ratios free from kinetic energy distortion. We discuss our results relative to a wider range of partial ion yield results on CO (6,(7)(8)(9)(10)(11)25).…”
Section: Introductionmentioning
confidence: 94%
“…The CO molecule was chosen because its electronic spectroscopy and core level photofragmentation have been studied extensively, and because there have been several previous studies of the core level photofragmentation yields claiming quantitative results (6,7). Photoionization mass spectroscopy (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), photoelectron spectroscopy (16,17), electron-ion coincidence spectroscopy (18,19), and electron energy loss spectroscopy (20-24) measurements on CO were performed. The results are compared to an early time-of-flight photoionization mass spectrometry study, in which a very short extraction pulse was used to improve quantitative collection (6), and to (e,e + ion) coincidence measurements (7) simulating photoionization, which are generally accepted to produce branching ratios free from kinetic energy distortion.…”
Section: Introductionmentioning
confidence: 99%